Pembuatan Sabun Cair dari Minyak Sawit di Desa Batu Belah Kabupaten Kampar - Zuqni Meldha; Idral Amri; Zulfansyah Zulfansyah; Hari Rionaldo; Syamsu Herman; Nirwana Nirwana; Lisa Legawati; Salma Liska; Yogi Yolanda; Yola Bertilsya Hendri; Alltop Amri Ya Habib (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2025)
The demand for natural self-care products is rising as more people recognize the value of keeping healthy skin and protecting the environment. Cooking oil, which is a derivative of palm oil, is an ingredient that is easily found by people in Batu Belah Village, Kampar Regency. This material has great potential to be processed into value-added products such as liquid soap. This study focuses on the use of cooking oil as the primary ingredient for producing liquid soap, while also opening new economic opportunities for the village community. This initiative captured the interest of Batu Belah People.In an attempt to implement the technology, the community service team distribute the liquid soap to the neighborhood.